Modernization and Elasticity of Substitution in China’s Grain Production: Evidence from 1991 to 2023 - Pengju Wang; Guanghao Wu (Agriculture, 2025)
The intensive utilization of agricultural inputs is key to agricultural modernization. This study analyzed the elasticity of substitution among inputs in Chinese grain production (1991–2023) using a Translog production function, controlling for price disturbances. The key findings are as follows: (1) Complementary relationships exist between capital–fertilizer, capital–land, fertilizer–land, pesticide–land, and fertilizer–labor, while capital–pesticide, fertilizer–pesticide, pesticide–labor, and land–labor are substitutive. (2) The elasticity of substitution among agricultural inputs stabilizes over time, with substitutive and complementary relationships among most factors weakening after 2004. (3) Eastern and northeastern regions tend to substitute labor with capital more significantly, while central and western regions show a balanced interplay. (4) Nationwide trends in agricultural input shares indicate increasing mechanization, land-use efficiency, fertilizer use, and reduced labor input. These results provide insights for optimizing input allocation and enhancing food security.